Preparation of porous graphene oxide/hydrogel nanocomposites and their ability for efficient adsorption of methylene blue. Issue 13 (26th January 2016) - Pourjavadi, Ali; Nazari, Mojtaba; Kabiri, Bahareh; Hosseini, Seyed Hassan; Bennett, Craig
Abstract : Porous nanocomposite hydrogels were prepared using CaCO3 particles as solid porogens. Abstract : Porous nanocomposite hydrogels were prepared using CaCO3 particles as solid porogens. The hydrogels were prepared by polymerization and grafting of acrylamide and 2-acrylamido-2-methylpropane sulfonic acid onto the starch in the presence of CaCO3 and graphene oxide. CaCO3 solid porogens were then removed by washing with acid and porous structures were obtained. The prepared hydrogels were used as adsorbents for methylene blue as a model cationic dye; and a very high adsorption capacity, up to 714.29 mg g −1, was obtained. Kinetics and isotherms of adsorption and the effect of porosity of hydrogel as well as other experimental conditions were also investigated. The prepared adsorbents were recovered and reused for several cycles, and high removal efficiency was observed even after five cycles of adsorption.